BENZATHINE PENICILLIN G INTRAMUSCULAR SUCCESSFUL TREATMENT OF OCULAR SYPHILIS WITH HUMAN IMMUNODEFICIENCY VIRUS POSITIVE : A CASE REPORT (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2020)
Introduction: Ocular Syphilis is a manifestation of multisystemic chronic infection caused by the spirochete Treponema pallidum, it can affect all structures and may present as anterior uveitis, posterior uveitis, panuveitis, retinitis, papillitis, making it ?a great masquerader?. Objective : To report successful treatment of ocular syphilis co infection with human immunodeficiency virus positive with Benzathine Penicillin G intramuscular. Case Presentation : A 28 year old man (heterosexual) presented with painless blurring of his eyes of three month?s duration. His visual acuity was hand movement in his right eye and 1/60 in the left with no dermatology lesion, funduscopy finding papillitis and vitreous cells in both eyes with retinal vasculitis and intraretinal hemorrhage in inferior region in left eye, serological tests revealed VDRL and TPHA test positive with ELISA was positive for human immunodeficiency virus. The patient immediately treated with benzathine penicillin G 2.4 million units intramuscularly once weekly for three consecutive weeks and antiretroviral. After three weeks, his visual acuity showed improvement and decreased VDRL titer three months later. Conclusion: Ocular Syphilis with HIV positive is curable with Penicillin G Intramuscular, with early detection and treatment are important for a good visual outcome.